2013
DOI: 10.1039/c3cy00487b
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine decorated graphene oxide-supported Ni1−xFex bimetallic nanoparticles as efficient and robust electrocatalysts for hydrazine fuel cells

Abstract: A very efficient, in situ growth approach has been developed to fabricate a graphene oxide (GO)-supported, highperformance Ni 1−x Fe x loading electrocatalyst. Transition metal nanoparticles (NPs) such as Ni are quite attractive due to their advantages in cost, and excellent electrocatalytic activity for hydrazine electrooxidation. However, their strong aggregation propensity makes it difficult to develop them into highly efficient electrocatalysts.Polyethyleneimine (PEI), a branched polyelectrolyte, is devise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Interestingly, it can be observed that these peaks are coincidently appeared between bulk Pt (JCPDS-04-0802) and Pd (JCPDS-46-1043), further showing the alloyed nature of Pt with Pd [31]. Furthermore, there is almost no any other peak emerged for porous PtPd NFs-RGO, which is much distinguished from that of GO with a sharp peak centered at 11 corresponding to the (0 0 1) planes of graphite oxide [32], evidencing the efficient removal of oxygenous functional groups from RGO during the reduction process [13].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, it can be observed that these peaks are coincidently appeared between bulk Pt (JCPDS-04-0802) and Pd (JCPDS-46-1043), further showing the alloyed nature of Pt with Pd [31]. Furthermore, there is almost no any other peak emerged for porous PtPd NFs-RGO, which is much distinguished from that of GO with a sharp peak centered at 11 corresponding to the (0 0 1) planes of graphite oxide [32], evidencing the efficient removal of oxygenous functional groups from RGO during the reduction process [13].…”
Section: Resultsmentioning
confidence: 75%
“…Raman analysis was performed to characterize the electronic and structural properties of graphite materials [32]. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The significant weight loss of GO, around 28% between 100 and 300 °C, was mainly due to the removal of oxygen-containing functional groups, just like C–O and C=O. And the weight loss within 100 °C which came from the escape of water molecules between the RGO nanosheets as well as the weight loss above 500 °C was due to the combustion of carbon skeleton [ 27 , 31 , 32 ]. The result indicated the removal of the oxygen-containing functional groups on Pd-Cu (P) /RGO and Pd-Cu (F) /RGO, which further confirms that GO was efficiently reduced to RGO during the synthesis [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The attachment of PEI at GO surface significantly affected the dispersion and size of the metal NPs. The electrochemical results indicated that the Ni 80 Fe 20 /PEI‐rGO hybrid exhibited superior catalytic activity over Ni 80 Fe 20 NPs directly deposited on GO in the hydrazine oxidation reaction . Further, Song et al.…”
Section: Two‐dimensional Materials As Catalyst Supportsmentioning
confidence: 94%